A review of history, production and storage of hydrogen (2021)
The need to reduce fossil fuel consumption has created opportunities for alternative fuels, including the migration of hydrogen as an unconventional alternative fuel. This alternative has more significant environmental and energy benefits due to the acquisition of raw materials and the integration of renewable energy sources. The research presents a review of historical evolution, a bibliometric analysis, and the processes used to produce and store this molecule. The POx and pyrolysis processes have the highest amount of research. At the same time, electrolysis is the process that has had the most significant growth, and research indicates that they allow greater sustainability due to the integration of renewable energies. Research trends indicate studies for integrating renewable energy resources and materials to improve chemical properties to increase capacity storage and decrease the risks due to high volatility.